2020
DOI: 10.1148/ryct.2020200028
|View full text |Cite
|
Sign up to set email alerts
|

Chest Imaging Appearance of COVID-19 Infection

Abstract: Key Points:1. It is important for all radiologists to be aware of the imaging spectrum of the disease and contribute to effective surveillance and response measures.2. Ground-glass opacities and consolidation can demonstrate an organizing pneumonia pattern. Cavitation can also occur in areas of airspace disease.This copy is for personal use only. To order printed copies, contact reprints@rsna.org I n P r e s s Abstract:COVID-19 (previously known as novel coronavirus [2019-nCoV]), first reported in China, has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
312
2
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(351 citation statements)
references
References 5 publications
20
312
2
17
Order By: Relevance
“…Interestingly, we observed a reversed halo sign in one patient (Fig. 3B), and a few similar cases have been reported in recent reports (19)(20)(21). The reversed halo sign was first regarded as specific for cryptogenic organizing pneumonia, and it can be seen in various infectious diseases, including angioinvasive pulmonary aspergillosis or mucormycosis, paracoccidioidomycosis, pneumocystis jiroveci pneumonia, and tuberculosis (22).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, we observed a reversed halo sign in one patient (Fig. 3B), and a few similar cases have been reported in recent reports (19)(20)(21). The reversed halo sign was first regarded as specific for cryptogenic organizing pneumonia, and it can be seen in various infectious diseases, including angioinvasive pulmonary aspergillosis or mucormycosis, paracoccidioidomycosis, pneumocystis jiroveci pneumonia, and tuberculosis (22).…”
Section: Discussionsupporting
confidence: 85%
“…The reversed halo sign was first regarded as specific for cryptogenic organizing pneumonia, and it can be seen in various infectious diseases, including angioinvasive pulmonary aspergillosis or mucormycosis, paracoccidioidomycosis, pneumocystis jiroveci pneumonia, and tuberculosis (22). This sign might reflect an organizing pneumonia pattern in COVID-19 pneumonia (21).…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al (41) found one patient with an initial normal chest CT that evolved into a new solitary, rounded peripheral GGO after three days. The reversed CT halo sign defined as a rounded area of ground glass surrounded by a complete or almost complete ring of consolidation can also be observed (16,49). Pleural effusion, lung cavitation, lymphadenopathy and calcification are rarely reported (40)(41)(42)(43)(44)(49)(50).…”
Section: Ct Imaging Findingsmentioning
confidence: 99%
“…This is reflected in the large number of case reports with very interesting aspects recently submitted to this journal. For example, Kong and Agarwal (10) report a series of three unrelated cases of COVID-19 pneumonia presenting with a spectrum of findings on chest radiograph and CT, varying from the commonly seen ground-glass opacities and consolidation, to patterns that include crazy paving and reversed halo, suggesting organizing pneumonia as the underlying mechanism of lung injury (11,12). In another report, Wu et al (13) show the temporal evolution on CT of a patient with COVID-19 infection, also presenting with radiologic findings resembling organizing pneumonia.…”
Section: N P R E S Smentioning
confidence: 99%